Penerapan Model Pembelajaran Think Aloud Pair Problem Solving (TAPPS) Berbantuan Video Animasi Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Pada Materi SPLDV Kelas X - Henry M. Sibarani; Mukhtar Mukhtar (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to improve students' mathematical problem solving abilities by using a learning model Think Aloud Pair Problem Solving (TAPPS) with the help of animated videos. The research was conducted at SMA Negeri 1 Sumbul involving 36 class X-G students as research subjects. The type of research used is classroom action research (PTK) with steps, namely, providing an initial test to measure students' mathematical problem solving abilities before taking action, identifying problems in the classroom, planning action, implementing action, namely applying the TAPPS learning model (Think Aloud Pair Problem Solving) With the help of animated videos as a medium for conveying summaries of learning material, observation, giving post tests, data analysis and data reflection. The research was carried out in 2 cycles where each cycle included two meetings, while observation activities were carried out simultaneously with the implementation of actions with the aim of observing the activities of researchers and students during learning activities. The research results showed that after the first cycle of research was carried out, the average student score from the pretest results to the first cycle posttest results increased from 52.56 to 72.94 with the average observation of student and researcher activities being 2.38 and 2.38. In the second cycle, students' mathematical problem solving abilities increased based on the average student score on posttest II, namely 84.62, the results of observations in the second cycle also improved better to 3.23 for student activities and 3.44 for researchers' ability to manage class, apart from that 34 out of 36 students (94%) obtained scores above the KKM (70). These results show that students' mathematical problem solving abilities increased after implementing the TAPPS learning model (Think Aloud Pair Problem Solving) Assisted by animated videos.